Identification and Evolutionary Relationship of Corynebacterium striatum Clinical Isolates - Jiao Wang; Jiao Pei; Mingming Liu; Rui Huang; Jiqiang Li; Shiying Liao; Jian Liang (Pathogens, 2022)
Corynebacterium striatum has developed into a new community-acquired and hospital-acquired multi-drug resistance (MDR) bacterium, and is a potential target pathogen for infection control and antibacterial management projects. In this study, non-duplicate samples of inpatients were collected from a local central hospital. Mass spectrometry showed that 54 C. striatum isolates mainly appeared in secretion and sputum from 14 departments. Protein fingerprint cluster analysis showed that the isolates were divided into four groups, most of which appeared in summer. The drug resistance test showed that all strains had multi-drug resistance, with high resistance rates to lincosamides, quinolones and tetracycline detected. Further analysis of the phylogenetic tree of C. striatum was conducted by cloning the 16S rRNA gene. It was found that isolates in the same department had high homology and tended to be located in the same branch or to be crossed in the same main branch. The strains in the same evolutionary branch group had the same drug resistance. Screening of site-specific recombinant elements revealed that 18 strains had integrase genes with the same sequence. This study shows that there may be mobile genetic elements in clinical isolates that drive gene exchange among strains, thus causing the cross-infection, spread and evolution of pathogenic bacteria in the hospital.